Amy / [videorecording (DVD)] (Lionsgate, 2015)
The incredible story of six-time Grammy winner Amy Winehouse - in her own words. Featuring extensive unseen archival footage and previously unheard tracks, this strikingly modern, moving, and vital film shines a light on our culture and the world we live in today.